Cost comparison by treatment arm and center‐level variations in cost and inpatient days on the phase III high‐risk B acute lymphoblastic leukemia trial AALL0232. (23rd December 2017) - DiNofia, Amanda M.; Seif, Alix E.; Devidas, Meenakshi; Li, Yimei; Hall, Matthew; Huang, Yuan‐Shung V.; Cahen, Viviane; Hunger, Stephen P.; Winick, Naomi J.; Carroll, William L.; Fisher, Brian T.; Larsen, Eric C.; et al.
Abstract: The Children's Oncology Group (COG) develops and implements multi‐institutional clinical trials with the primary goal of assessing the efficacy and safety profile of treatment regimens for various pediatric cancers. However, the monetary costs of treatment regimens are not measured. AALL0232 was a COG randomized phase III trial for children with acute lymphoblastic leukemia that found that dexamethasone (DEX) was a more effective glucocorticoid than prednisone (PRED) in patients younger than 10 years, but PRED was equally effective and less toxic in older patients. In addition, high‐dose methotrexate (HD‐MTX) led to better survival than escalating doses of methotrexate (C‐MTX). Cost data from the Pediatric Health Information System database were merged with clinical data from the COG AALL0232 trial. Total and component costs were compared between treatment arms and across hospitals. Inpatient costs were higher in the HD‐MTX and DEX arms when compared to the C‐MTX and PRED arms at the end of therapy. There was no difference in cost between these arms at last follow‐up. Considerable variation in total costs existed across centers to deliver the same therapy that was driven by differences in inpatient days and pharmacy costs. The more effective regimens were found to be more expensive during therapy but were ultimately cost‐neutral in longer term follow‐up. The variations in cost across centers suggest an opportunity to standardize resource utilization for patients receiving similar therapies, which could translate into reduced healthcare expenditures. Abstract : When comparing costs between treatment arms of the high‐risk B acute lymphoblastic leukemia pediatric trial, high‐dose methotrexate and dexamethasone arms were associated with higher costs when compared to the escalating methotrexate and prednisone arms during protocol therapy, but there was no difference in cost between the methotrexate or steroid arms at time of last follow up. We also found that costs vary significantly across hospitals to deliver identical therapy.